Racial cities : governance and the segregation of Romani people in urban Europe - Picker, Giovanni (Routledge advances in sociology, 2017)
Nodes -- Displacement -- Omission -- Containment -- Cohesion -- Correspondences -- Beyond segregation? -- Bibliography -- Index